Operations Management - Slack, Nigel; Brandon-Jones, Alistair; Burgess, Nicola (England: New York: Pearson, 2022)
"The text provides a clear, authoritative, well-structured and interesting treatment of operations management as it applies to a variety of businesses and organisations. The text provides both a logical path through the activities of operations management and an understanding of their strategic context. The distinctive features are: Clear structure, Illustrations-based, Worked examples, Critical commentaries, Responsible operations, etc"--
Includes bibliographical references and index.
Keywords: Production management; Manufacturing processes; Industrial management .